Teachers' Strategies in Overcoming Students' Learning Difficulties in IPAS Subjects - Difa Al Kaffi; Rosi Andani; Nanda Dwi Pamungkas; Maryam Maryam (Journal of Primary Education (JPE), 2025)
AbstractThis study aims to identify and analyze the strategies used by teachers in overcoming students' learning difficulties in the subject of IPAS in class 5 MIN 1 Bengkulu City. This study uses a qualitative method with data collection techniques through interviews, observations, and document analysis. The results of the study indicate that teachers use several strategies to overcome students' learning difficulties, namely: 1). Student-centered learning strategies, such as project-based learning and problem-based learning; 2). Use of varied learning media, such as multimedia, videos, and images; 3). Providing constructive and structured feedback to help students understand and overcome learning difficulties; 4). Cooperation with parents and school committees to increase participation and support for the learning process; 5). Use of information and communication technology (ICT) to improve access and quality of learning. This study also found that the factors that influence students' learning difficulties in the subject of science are: 1). Lack of student motivation and interest in learning; 2). Lack of students' cognitive and affective abilities; 3). Lack of support from parents and the environment; 4). Lack of quality learning and resources. This research is expected to contribute to the development of effective learning strategies in overcoming students' learning difficulties in science subjects in elementary schools, as well as providing recommendations for teachers, parents, and schools to improve the quality of learning and overcome students' learning difficulties.